2004
DOI: 10.1002/anie.200353424
|View full text |Cite
|
Sign up to set email alerts
|

Li–Cu Exchange in Intercalated Cu3N—With a Remark on Cu4N

Abstract: A surprising substitution of Cu by Li has been observed during the intercalation reaction of Cu3N with n‐butyllithium, besides an expected incorporation of Li. The twofold coordinated Cu+ ions are shifted into cuboctahedral cavities along with a reduction to Cu0 (see picture). The chemical bonding of the compounds LixCu3N is analyzed in comparison to Cu4N on the basis of band‐structure calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…According to first-principle calculations, the incorporation of an excessive metal atom at the center of each unit cell brings about metallic ternary compounds Cu 3 NM (M¼Ni, Cu, Zn, Pd, Ag, and Cd) [9]. Experimental investigations have shown that lithium [10] and palladium [11] can be successfully inserted to the cell centers in bulk Cu 3 N; on the other hand, the effect of copper [12], titanium [13], hydrogen [14], and silver [15] dopants on the physical properties of Cu 3 NM thin films has also been reported by various researchers. Light doping with Ti atoms seems to raise the decomposition temperature of Cu 3 N films to 300-350 1C [13], while the electrical conductivity of hydrogen-implanted Cu 3 N films may increase by more than two orders of magnitude [14].…”
Section: Introductionmentioning
confidence: 99%
“…According to first-principle calculations, the incorporation of an excessive metal atom at the center of each unit cell brings about metallic ternary compounds Cu 3 NM (M¼Ni, Cu, Zn, Pd, Ag, and Cd) [9]. Experimental investigations have shown that lithium [10] and palladium [11] can be successfully inserted to the cell centers in bulk Cu 3 N; on the other hand, the effect of copper [12], titanium [13], hydrogen [14], and silver [15] dopants on the physical properties of Cu 3 NM thin films has also been reported by various researchers. Light doping with Ti atoms seems to raise the decomposition temperature of Cu 3 N films to 300-350 1C [13], while the electrical conductivity of hydrogen-implanted Cu 3 N films may increase by more than two orders of magnitude [14].…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of the nitrides was significantly developed during the period between the 1930s and 1970s by a number of scientists, including Juza [5]. More recent studies have advanced our knowledge by reporting the synthesis of novel ternary nitrides containing alkaline-earth and transition metal elements [6,7], the unique electronic structure of alkaline-earth nitrides [8], Li intercalation [9,10], large crystal growth of GaN using Na flux [11], and novel Sr-containing nitrides [12,13]. For transition metal binary nitrides, a wide variety of physical properties has * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…[17] When the metastable Cu 3 N is heated, it decomposes into metallic copper and nitrogen gas, a behavior that could be exploited in copper metallization. [18,19] Cu 3 N is also expected to be a good host material for Li or Cu atoms, [20] since it exhibits the anti-ReO 3 structure, which is rather open with the Cu atoms occupying the midpoints of the edges and the N atoms occupying the cell corners. The experimentally measured band gap (indirect) for Cu 3 N films seems to be dependent upon the nitrogen content, and has been reported to be in the range 1.3-2.1 eV.…”
Section: Introductionmentioning
confidence: 99%